(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Poor posture is almost every office worker’s health problem. It is due mainly to inadequate office equipment and a lack of awareness. One of the disorders that a lousy posture brings to the table is back pain. It is primarily because of the nature of passive work. Stress and strain resulting from manual animal handling are among the most common conditions that adversely affect employees’ health for Research purposes. The ABC Animal Clinic employees associated with demanding manual tasks may result in increased occupational injuries, worker fatigue, absenteeism, poor human performance, and decreased productivity. The employees of the ABC Animal Clinic have a collaborative approach to their work, which is excellent for building a positive and productive work environment. By allowing each other to help with various tasks, they can work more efficiently and effectively, reducing stress and preventing burnout. In addition to improving individual job satisfaction, when individuals cooperate to achieve a common objective, they develop stronger relationships and a greater sense of trust and respect for one another. Overall, this kind of collaborative work culture can be a significant asset for any organization, and it’s great to see the employees of the ABC Animal Clinic taking steps to support each other in their work. Findings revealed that the employees of ABC Animal Clinic perform a range of tasks efficiently, promote a good working environment, and prevent themselves from getting injured. Their types of equipment are always clean. However, the employees experience Unorganized and uneasy reaching Equipment, Foul smell that affects their productivity, some animal patients cannot avoid experiencing stress while being held, and some employees experience awkward postures. The researchers analyzed collected data to establish utilization in creating ergonomic development to improve employees’ productivity, which will help them increase their Morale, Motivation, and Performance. This can benefit both employees and the organization by developing more Effective ergonomics.